EVALUATION OF REGENERATIVE THERAPY USING CELL SHEET THROUGH CEMENTUM PROTEIN-1 EXPRESSION ON MACACA NEMESTRINA - Astuty, Syanti Wahyu; Sunarto, Hari; Amir, Lisa; Idrus, Erik (International Journal of Applied Pharmaceutics, 2018)
Objective: The main objective of periodontal therapy is tissue regeneration. Previous studies have identified the potential of mesenchymal stem cells to improve major periodontal defect reconstruction in bone tissue engineering. Cell sheet technology (CST), in which a cell culture is obtained from a material coated with a temperature-sensitive substrate, has been developed for the reconstruction of various tissues, including periodontal tissue. Cementum protein-1 (CEMP-1) is a 50-kDa protein that plays a crucial role in cementogenesis by enhancing the combining of cells formed by cell cementoblast. Evaluate periodontal tissue regeneration with CST, and the application of chitosan, chitosan cell sheet or arginineglycineaspartic acid (RGD)-modified chitosan cell sheet on Macaca nemestrina one-wall defect model. Methods: The CEMP-1 was analyzed expression in a sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) gel electrophoresis assay. Results: CEMP-1 expression in gingival crevicular fluid was observed using the SDS-PAGE method every week for 3Â weeks. Protein band expressions on SDS-PAGE gel were identified at around 50Â kDa with different thicknesses between groups. The chitosan, chitosan cell sheet, and RGD-modified chitosan cell sheet groups showed protein bands of CEMP-1 between 50 and 70Â kDa at weeks 1, 2, and 3; weeks 2 and 3; and weeks 1 and 2, respectively. Conclusion: Our results demonstrated that the application of chitosan and RGD-modified chitosan cell sheets could enhance bone regeneration, as evidenced by CEMP-1 protein expression levels.